EXPRESSION OF SOCS3 AND SOCS5 MRNAS IN PERIPHERAL BLOOD MONONUCLEARS FROM THE PATIENTS WITH BRONCHIAL ASTHMA - V. V. Lim (SPb RAACI, 2014)
We observed sixty patients with allergic bronchial asthma (ABA) and 54 with non-allergic bronchial asthma (NABA). Quantitative SOCS3 and SOCS5 mRNA expression was evaluated by means of real-time PCR. Eighteen healthy persons served as a control group. In patients with bronchial asthma (irrespectively of pathogenetic form), a significant increase of SOCS3 transcription factor expression was detected in peripheral blood mononuclears, as compared with control group. This increase was more pronounced in NABA group. The mRNA SOCS5 level was significantly decreased in bronchial asthma patients, as compared to control group, especially, in ABA subgroup rather than in NABA patients. Thus, an increased expression of SOCS3 mRNA in BA patients could be regarded as a protective antiinflammatory response Decrease of SOCS5 mRNA expression in patients with bronchial asthma (being more pronounced in ABA), may be indicative for a deficiency in negative feedback regulation of gene transcription in allergic bronchial asthma.